2010
DOI: 10.1002/jsfa.4004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary yeast autolysate (Saccharomyces cerevisiae) on performance, egg traits, egg cholesterol content, egg yolk fatty acid composition and humoral immune response of laying hens

Abstract: Dietary yeast autolysate at levels of 2, 3 and 4 g kg(-1) had beneficial effects on performance, egg cholesterol content and humoral immune response. It is concluded that 2 g kg(-1) yeast autolysate will be enough to have beneficial effects in laying hens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 23 publications
8
26
0
1
Order By: Relevance
“…Moreover, the egg concentrations of vitamin A, crude fat, vitamin E, calcium, zinc, selenium, and dry matter also dramatically improved in the eggs of yeastfed hens (Table 5). Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, the egg concentrations of vitamin A, crude fat, vitamin E, calcium, zinc, selenium, and dry matter also dramatically improved in the eggs of yeastfed hens (Table 5). Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 83%
“…Yeast and yeast products may also serve as alternatives to antibiotics to promote growth and disease resistance in poultry (Yalçin et al, 2010). In recent years, there has been an increasing number of reports documenting the use of various yeast strains and yeast products, such as inactive dried yeast, yeast culture, whey yeast, selenium yeast, chromium yeast and yeast cell walls, in the diets of laying hens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the yeast is also used as a feed supplement in poultry rations that can stimulate the growth process (Yalçın et al, 2013). The use of yeast in the feed has been widely studied and have a significant effect on performance and physiological responses to poultry, such as increasing the immune response (Asli et al, 2007;Yalçın et al, 2010;Haldar et al, 2011), lowering the blood cholesterol levels (Yalçın et al, 2010) and increasing the digestibility of nutrients (Gao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports about the usage of various yeast and yeast products such as inactive dried yeast, yeast culture, whey yeast, selenium yeast, chromium yeast and yeast autolysate in the diets of laying hens on performance (13,31,32,34). Yalçın et al (2010) concluded that dietary yeast autolysate at the levels of 2, 3 and 4 g/kg had beneficial effects on performance, egg cholesterol content and humoral immune response.…”
Section: Introductionmentioning
confidence: 99%